Effects of enriched-potassium diet on cardiorespiratory outcomes in experimental non-ischemic chronic heart failure - Schwarz, Karla G.; Pereyra, Katherin V.; Toledo, Camilo; Andrade, David C.; Díaz, Hugo S.; Díaz-Jara, Esteban; Ortolani, Domiziana; Rios-Gallardo, Angélica; Arias, Paulina; Heras, Alexandra Las; Vera, Ignacio; Ortiz, Fernando C.; et al. (My University, 2021)
Abstract Background: Chronic heart failure (CHF) is a global health problem. Increased sympathetic outflow, cardiac arrhythmogenesis and irregular breathing patterns have all been associated with poor outcomes in CHF. Several studies showed that activation of the renin-angiotensin system (RAS) play a key role in CHF pathophysiology. Interestingly, potassium (K+) supplemented diets showed promising results in normalizing RAS axis and autonomic dysfunction in vascular diseases, lowering cardiovascular risk. Whether subtle increases in dietary K+ consumption may exert similar effects in CHF has not been previously tested. Accordingly, we aimed to evaluate the effects of dietary K+ supplementation on cardiorespiratory alterations in rats with CHF. Methods: Adult male Sprague–Dawley rats underwent volume overload to induce non-ischemic CHF. Animals were randomly allocated to normal chow diet (CHF group) or supplemented K+ diet (CHF+K+ group) for 6 weeks. Cardiac arrhythmogenesis, sympathetic outflow, baroreflex sensitivity, breathing disorders, chemoreflex function, respiratory– cardiovascular coupling and cardiac function were evaluated. Results: Compared to normal chow diet, K+ supplemented diet in CHF significantly reduced arrhythmia incidence (67.8 ± 15.1 vs. 31.0 ± 3.7 events/hour, CHF vs. CHF+K+), decreased cardiac sympathetic tone (ΔHR to propranolol: - 97.4 ± 9.4 vs. - 60.8 ± 8.3 bpm, CHF vs. CHF+K+), restored baroreflex function and attenuated irregular breathing patterns. Additionally, supplementation of the diet with K+ restores normal central respiratory chemoreflex drive and abrogates pathological cardio-respiratory coupling in CHF rats being the outcome an improved cardiac function. Conclusion: Our findings support that dietary K+ supplementation in non-ischemic CHF alleviate cardiorespiratory dysfunction.
Keywords: heart failure; potassium supplemented diet; autonomic imbalance; breathing disorders; chemoreflex function